Rare variant of ovotesticular disorder of sex development diagnosed due to injury-induced rupture of the reproductive gland in a patient with SRY-negative 46,ХХ karyotype (clinical case) - A. B. Okulov; E. A. Volodko; O. Yu. Latyshev; D. N. Godlevsky; E. V. Timokhovich; K. K. Mirakov; K. S. Nikitin; A. V. Anikiev (Андрология и генитальная хирургия, 2021)
The clinical case of a rare variant of disorder of sex development (DSD) is described. This disorder was diagnosed with an emergency operation for the traumatic rupture of the gonad. A patient (14 years old) with a male phenotype and lack of muller duct derivatives had a female SRY negative karyotype (46,XX) and an ovotesticular gonad structure as a result of duplication in the regulatory zone of the SOX9 gene. Ovotesticular disorders of sex development with karyotype 46,XX, as a rule, are accompanied by an ambiguous genitalia and derivatives of the muller structures. Early diagnosis of the described variant of DSD was difficult due to the development of male type genitalia. Timely identification of DSD including the presented option of DSD, is possible during routine examinations of the urologist with mandatory ultrasound examination of the scrotum and pelvis.